1990
DOI: 10.1002/hep.1840110319
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of the Order of Revascularization in Liver Grafting

Abstract: A study was conducted comparing the effects of initial arterialization vs. initial portal revascularization in unstored warm ischemic (for 30 min) livers, livers stored for 4 hr at 0 degrees C in Collins solution and livers rendered warm ischemic for 1 hr before removal and replacement as autografts. All livers that received initial arterialization showed uniform diffuse perfusion, whereas those with initial portal perfusion were patchy and well perfused only in the right lobe. In the experimental animal, init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…In a prospective randomized study, Ducerf et al7 showed more stable hemodynamics (assessed by mean arterial pressure, central venous pressure, cardiac index, systemic vascular resistance, and pulmonary capillary pressure) and lower peak values of serum aspartate aminotransferase after IAR, compared to IPR. Similar to previous animal studies,1 they also observed a more homogenous graft reperfusion in the IAR group. No differences were found between the IAR and IPR group with respect to the intraoperative blood products required for transfusion or the use of antifibrinolytic drugs.…”
Section: Influence Of Reperfusion Sequence On Hemodynamics and Metabosupporting
confidence: 88%
See 1 more Smart Citation
“…In a prospective randomized study, Ducerf et al7 showed more stable hemodynamics (assessed by mean arterial pressure, central venous pressure, cardiac index, systemic vascular resistance, and pulmonary capillary pressure) and lower peak values of serum aspartate aminotransferase after IAR, compared to IPR. Similar to previous animal studies,1 they also observed a more homogenous graft reperfusion in the IAR group. No differences were found between the IAR and IPR group with respect to the intraoperative blood products required for transfusion or the use of antifibrinolytic drugs.…”
Section: Influence Of Reperfusion Sequence On Hemodynamics and Metabosupporting
confidence: 88%
“…Various reperfusion protocols have been analyzed in 3 experimental studies, using different animal models 1–3. Hickman and Innes1 compared 2 sequential protocols in pigs: initial arterial revascularization (IAR) vs. initial portal revascularization (IPR). These investigators found better homogenous perfusion of the liver graft after IAR, compared to IPR.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Leukocyte accumulation in simultaneous reperfused sinusoids and postsinusoidal venuoles was decreased by 17% and 64%, respectively [21]. On the other hand, several clinical studies have shown an advantage for liver allografts being re‐arterialized before portal reperfusion [47–50]. One experimental study showed that the major part of reperfusion injury is constituted during the portal venous reperfusion and that this injury can be, at least partially, attenuated by initial arterial reperfusion [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, several clinical and experimental studies have shown an advantage for liver allografts rearterialized before portal reperfusion. 4,7,8,13 In this study, we investigated the impact of the timing of rearterialization in liver transplantation using more sensitive parameters of injury, including markers of hepatocellular injury, reperfusion injury, and endothelial cell function.…”
Section: Discussionmentioning
confidence: 99%